The Legal Certainty principle in the Real State Regulation - Cervantes López, René Santos (2020)
This article analyzes the importance of Legal Certainty in the context of transferring Real State and how it affects basic entitlements or covenants of living in peace, and quiet enjoyment. The text explains the difficulty to conceptualize these rights and their necessary protection. Furthermore, Civil Law regulations provide the legalframework to examine Real State institute.